The Potency of Iles-iles for Conserving Forest, and Increasing Revenue and Tourism in Ancient Volcano, Nglanggeran Gunung Kidul - Sumarwoto, Sumarwoto; Poerwanto, Mofit Eko (Proceeding International Conference on Global Resource Conservation, 2013)
Iles-iles are often referred to as porang or yellow iles or Amorphophallus muelleri blume. The plant is potentially for agro-forestry development and their tubers are used as a functional food, and raw materials of various types of industries. The plant is expected to increase income and welfare of forest communities. The forest around ancient volcano Nglanggeran Gunungkidul has potency as a tourist attraction. The forest is situated at an altitude 400 M asl, with an area of approximately 30 Ha. Tourism potential will increase with the presence of agro-forestry iles-iles. Increased potency is expected to provide added value to the local community in particular and the district government of Gunungkidul in general. In addition, it is hoped that a variety of benefits that have been mentioned, will not decimate the forest as a source of oxygen that contributed as the lungs of the world. This information is expected to be useful for researches and government of Gunungkidul in increasing communityâs income, developing agro-forestry, conserving forest, and developing tourism.Â Key words: ancient volcano, forest conservation, iles-iles, income, tourismÂ